Pengaruh Gaya Kepemimpinan Dan Budaya Organisasi Terhadap Kinerja Karyawan di Divisi Human Capital Management PT Bank Central Asia, Tbk - Agnes Mega Kosasih; Eko Harry Susanto (Universitas Tarumanagara, 2019)
Along with the changing times and changes in consumer behavior in today's digital era, it encourages companies to adapt, not only from external factors but also from the company's internal factors. Existing leadership methods must be able to connect employees from different ages and backgrounds. In addition to leadership style, organizational culture is also an important consideration in today's business competition. This study aims to know and analyze simultaneously the influence of leadership style and organizational culture on the performance of employees in the Human Capital Management Division of PT Bank Central Asia, Tbk. This study uses quantitative analysis methods. Data collection was carried out with questionnaires distributed to employees of the Human Capital Management division at PT Bank Central Asia, Tbk. This study uses multiple linear analysis.